Smart technology and the meaning in life of older adults during the Covid-19 public health emergency period: a cross-cultural qualitative study - von Humboldt, Sofia; Mendoza-Ruvalcaba, Neyda Ma.; Arias-Merino, Elva Dolores; Costa, Andrea; Cabras, Emilia; Low, Gail; Leal, Isabel (My University, 2020)
The exponential increase of the older segment of the population is coinciding with the growing challenges of a digital society in different socio-cultural contexts. This exploratory study aims to analyze older adult perspectives of how smart technology influenced their meaning in life during the Covid-19 Public Health Emergency period, using qualitative research at a cross-national level. Three hundred and fifty-one community-dwelling older participants aged 65¿87 years were included in the study. Participants were Italian, Mexican, Portuguese and Spanish. All the narratives went through a process of content analysis. Findings of content analysis produced six themes: Meaningful relations, rewarding activities, spirituality, health and safety-related support, self-growth, and physical activity. Smart technology was important in promoting significant relations for Mexican older adults (71.3%), rewarding activities for Portuguese older adults (57.1%), spirituality for Spanish older participants (71.6%), and physical activity for Italian older adults (29.5%). This study indicated that smart technology during the Health Emergency period was important for the meaning in life of older populations, mostly by facilitating meaningful relations, rewarding activities and spirituality. Future interventions with older adults during pandemic periods should consider the diversity of themes associated with increasing older adult well-being, from a cross-cultural perspective.